3D‐printed Electrochemical Sensor for Organophosphate Nerve Agents. Issue 1 (10th August 2022) - Jyoti,; Redondo, Edurne; Alduhaish, Osamah; Pumera, Martin
Abstract: 3D‐printing has revolutionized various industries and scientific research by its substantial benefits such as fast prototyping, high accuracy, durability, and customized shapes. Fused deposition modeling has been used in the fabrication of 3D‐printed nanocarbon electrodes. Utilization of these 3D‐printed nanocarbon electrodes in the identification of organophosphates (OPs) such as parathion, methyl parathion, paraoxon, and fenitrothion, has not been reported. These compounds are highly toxic and used as chemical warfare agents and pesticides. Herein, we show that 3D‐printing can be utilized for low‐cost and diagnosis of priority nerve agents. Abstract :